Bibliometric Analysis and Visualization of Bootstrapping Strategy Articles by Indonesian Authors - Suci, Rahayu Puji; Iswari, Hanif Rani; Purwanto, Arief; Sodik, Sodik; Kirana, Prambayu Candra; Ainun, Siti Nur (Bulletin of Management and Business, 2023)
This research aims to analyze bibliometric characteristics and trends of crowdfunding bootstrapping strategy articles indexed by Indonesian authors. Information was extracted from the Google Scholar database. The study employed bootstrapping and its variations as search terms, with Indonesian author affiliations considered. Simple statistical techniques were applied, and VOS Viewer software was utilized for bibliometric analysis. In this study, patterns of keyword co-occurrence, document citations, citation relationships, and bibliographic coupling were visualized. The results indicate that the main trend in current startup research is the adoption of bootstrapping strategy, particularly network-based bootstrapping, due to its ability to support startup growth without relying on external funding but rather on a network.